Selective extraction of magnesium from asbestos-containing raw materials - Fomin, V.N.; Dyussekeyeva, A.T.; Minayeva, Ye.V.; Amanzholova, B.A.; Kassymov, M.E.; Rozhkovoy, I.Ye.; Kargina, N.A. (KSU Publ., 2018)
In this work, great attention was paid to identifying the reasons for the absence of practically implemented technologies for processing chrysotile asbestos wastes and searching for new methods for treating wastes with the aim of obtaining magnesium and other useful products of commercial interest. A series of experiments with solutions of ammonium chloride of different concentrations was carried out to study the kinetics of magnesium leaching. The concentration of magnesium leached increases with the concentration of the NH4Cl solution (CMg = 0.092M; CMg = 0.1M; CMg = 0.102M), as well as with the time of the process itself. It was shown that the difference between the leaching rates of magnesium by 3M and 5M NH4Cl solutions was not significant, and it was rather large for 1M and 3M solutions. The study of the thermodynamics of magnesium leaching was carried out with 3 molar solution of ammonium chloride at various temperatures. Graphs of the concentration of leached magnesium versus the leaching time at different temperatures of the ammonium chloride solution were plotted based on the results obtained. Experiments showed that the degree of magnesium leaching from asbestos increased with increasing temperature. The activation energy was calculated, which was equal to 44 kJ. Sediment identification was carried out using a laser-atomic emission spectrometer apparatus. The results of the experiment showed that a certain amount of magnesium, calcium and a small amount of other metals were contained in the obtained precipitates. Admixture of calcium does not affect the properties of the precipitate obtained. Leaching tests carried out with the help of ammonium chloride solution of various concentrations showed that the fibrous structure of asbestos was not destroyed.
Асбестқұрамды шикізаттан магнийді селективті бөліп алу əдісі
Селективное извлечение магния из асбестосодержащего сырья
Keywords: selective extraction of magnesium; asbestos-containing raw materials; kinetics; thermodynamics; concentration; magnesium-ammonium phosphate; activation energy; leaching